Membedah Komodifikasi Isi Pesan Mini Drama Line “Nic And Mar” (Analisis Semiotika John Fiske Terhadap Mini Drama Line) - Indra Hutami; Freddy Yusanto; Catur Nugroho (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Mobile mini drama of the Line is a mini-series that narrate the characters who play a part in a story which has drama genre. One of them is a mobile mini drama Line "Nic and Mar" designed to meet the needs of the people of Indonesia will of entertainment that can be enjoyed anytime, anywhere for free just by using the gadget. However, the facts behind their mobile mini dramas which incidentally can be enjoyed free, able to bring great benefits in terms of economy for the media Line. Researchers interested in studying this phenomenon because the researchers identified that there has been a process of commodification and wanted to know what kind of shape the commodification. The purpose of this research is to determine how to shape the content of the message commodification Mini Drama Line "Nic and Mar". The approach of the research is qualitative, uses a semiotic analysis to analyze the research object. The data analysis technique is based from “The Codes of Television” by John Fiske. The research result is in Mini Drama Line "Nic and Mar" there are audio aspect and visual aspect that formed by videography techniques so that it becomes a spectacle, but the signs are there in processed into a product so that the scene in this drama mini formed into commodities. The function changed, initially the storyline is used for forming part mini-drama story, now the storyline also serves as a exchange rate.